2017
DOI: 10.1016/j.prosdent.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Color stability of ceramic laminate veneers cemented with light-polymerizing and dual-polymerizing luting agent: A split-mouth randomized clinical trial

Abstract: The color stability of ceramic laminate veneers was similar for both of the polymerizing modes for all evaluated periods. Marginal discoloration increased over a 2-year period for both the light- and the dual-polymerizing modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 29 publications
4
48
1
6
Order By: Relevance
“…[ 10 11 ] These changes can be evaluated by spectrophotometers, equipment that eliminates subjective interpretations by the naked eye,[ 11 17 ] and by CIE L*a*b* system, used to evaluate the color of dental materials. [ 18 ] Tooth color changes can be expressed by ΔE, where a value above 3.7 characterizes tooth color change perceptible to the naked eye. [ 17 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 ] These changes can be evaluated by spectrophotometers, equipment that eliminates subjective interpretations by the naked eye,[ 11 17 ] and by CIE L*a*b* system, used to evaluate the color of dental materials. [ 18 ] Tooth color changes can be expressed by ΔE, where a value above 3.7 characterizes tooth color change perceptible to the naked eye. [ 17 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Invitro study by Çağrı Ural et al 2016 showed that the color change of both light cure and dual cure adhesive resin cement were within clinically accepted level also, third-generation adhesive resin cements with free tertiary amines and benzoyl peroxide underwent smaller color changes than the light-and dual-cure resin materials 3 Marchionatti et al 2017 concluded that The light-and dualpolymerizing modes presented similar color changes for all evaluated periods (2, 6, 12, and 24 months). 20 Also, Ah-Rang Kim, et al 2015 said that the color change of selfcure and dual cure adhesive resin cement caused by the amine group 21 Also, Evren Kilinc et al 2011 concluded that all resin cements did not cause a noticeable color change on the ceramic, which also showed that even a significant color change of the resin cement may be unnoticeable when covered by the ceramic. 2…”
Section: Discussionmentioning
confidence: 99%
“…However, especially for veneers, the use of purely light curing flowable composites was described, because a chemical initiating system used in the dual curing products was claimed to have a tendency for discoloration over time. However, recently no difference was found in a clinical study related to color stability between a light cured resin composite and a dual curing luting material [40]. If veneers are luted with light curing only materials, the optimal quality of cure (polymerization) has to be guaranteed.…”
Section: Dual Curing or Light Curing Only?mentioning
confidence: 99%